2018
DOI: 10.2478/picbe-2018-0067
|View full text |Cite
|
Sign up to set email alerts
|

The influence of personality types on the impulsive buying behavior of a consumer

Abstract: The relation between the personality of consumers and their buying behavior has been a very much debated topic in the field of marketing researches. Several studies have shown that personality has a significant influence on the way consumer behave in their social and economic environment, in the way they approach and accept innovations and new developed products or even in their shopping behavior. This paper presents the influence of the Myers-Briggs personality dichotomies on the impulsive consumer behavior a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 36 publications
2
9
0
Order By: Relevance
“…The dichotomous division of purchasers according to personality types based on the classification proposed by Briggs-Myers and Briggs (2020) was considered by Pelau et al (2018), but it was analyzed it only in relation to shopping behavior. The authors focused on the impact of the division of purchasers into extroverts and introverts on impulsive purchases and purchases of newly promoted products.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dichotomous division of purchasers according to personality types based on the classification proposed by Briggs-Myers and Briggs (2020) was considered by Pelau et al (2018), but it was analyzed it only in relation to shopping behavior. The authors focused on the impact of the division of purchasers into extroverts and introverts on impulsive purchases and purchases of newly promoted products.…”
Section: Discussionmentioning
confidence: 99%
“…Until now, however, research studies have been conducted into the impact of personality types only on shopping behavior. Their results indicate that extroverts are open to buying new products and / or to making unplanned purchases (Pelau et al, 2018), acquiring IT novelties (Dinsmore et al, 2017), as well as buying products of global brands (Zabkar et al, 2017). The results of the analysis of the world literature on the subject indicate that until now, the joint creation of marketing values by offerors and purchasers has not been considered in the context of a type of personality manifested in a specific lifestyle.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Kostelic (2019) studied 244 participants through an online questionnaire and found that J/P dichotomy is a significant variable contributing to one's decision making and attitude towards solving problem independently or choosing an advisor for help in legal and financial situation. Pelau, Serban & Chinie (2018) acquired 207 valid questionnaires through survey carried out in an urban population, and they found that J/P dichotomy has a significant role on impulsive buying behavior. This result is supported by Yoon & Lim (2018) where the effect of BFI and MBTI on impulsive and compulsive online buying behavior were compared using 296 questionnaires obtained from online shopping mall users in Korea.…”
Section: Significance Of Judging-perceiving Dichotomymentioning
confidence: 99%
“…Large scale self-reported personality assessment results had been made available conveniently through the means of datamining on social media platform. This is evident through Plank & Hovy (2015), where dichotomy alone is enough to infer insightful behaviors (Kostelic, 2019;Pelau, Serban & Chinie, 2018;Yoon & Lim, 2018;Wei et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Internal factors include attitude, beliefs, demographics, feelings, lifestyle, motivation, and personality traits, whereas external factors include culture, locality, and the reference group ( Sandhusen, 2000 ). Many previous studies have researched personality in consumer behavior, like brand preferences ( Banerjee, 2016 ), impulsive buying behavior ( Pelau et al, 2018 ; Sofi and Najar, 2018 ), online purchase intentions ( Iqbal et al, 2021 ), and travel-related consumer-generated media ( Yoo and Gretzel, 2011 ). Only a select few studies have focused on the personality of the consumer in a virtual environment, examining, for instance, shyness as a personality trait in a virtual world ( Hammick and Lee, 2014 ), the effects of different interior architectural forms on emotional states by considering personality traits in a VR setup ( Banaei et al, 2019 ), presence measure ( Kober and Neuper, 2013 ), consumer attitudes in AR ( Srivastava et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%